2010
DOI: 10.1007/s10641-010-9716-8
|View full text |Cite
|
Sign up to set email alerts
|

Displacement, velocity preference, and substrate use of three native California stream fishes in simulated pulsed flows

Abstract: We studied whether juvenile fishes were able to maintain swimming speed and position during simulated river pulsed flows in a laboratory flume. We used a glass flume (15.24×0.6 m) with riverrock substrate to determine the longitudinal displacement, movement distances and frequencies, velocity selection, and substrate use of juvenile (SL range: 6.1± 0.2 cm) hardhead Mylopharodon conocephalus (n=13), rainbow trout Oncorhynchus mykiss (n=11), and Sacramento sucker Catostomus occidentalis (n=12) during a 100-min f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 22 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…Similarly, in a simulated pulsed‐flow study conducted in an experimental flume, under increasing flow velocities, three juvenile stream fishes (cyprinid, salmonid, and catastomid) swam faster and also hid in the available rocky substrate, presumably to conserve energy (Chun et al, ). Under maximum velocities up to 0.46 m s −1 , those juveniles were able to maintain their swimming speed and hold position (Chun et al, ), whereas in the present study, those activities were possible under velocities up to 0.72 m s −1 . Both the presence of deflectors and the shorter duration peak flow stimulus in the present study may have ameliorated the potential negative effects of higher velocities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a simulated pulsed‐flow study conducted in an experimental flume, under increasing flow velocities, three juvenile stream fishes (cyprinid, salmonid, and catastomid) swam faster and also hid in the available rocky substrate, presumably to conserve energy (Chun et al, ). Under maximum velocities up to 0.46 m s −1 , those juveniles were able to maintain their swimming speed and hold position (Chun et al, ), whereas in the present study, those activities were possible under velocities up to 0.72 m s −1 . Both the presence of deflectors and the shorter duration peak flow stimulus in the present study may have ameliorated the potential negative effects of higher velocities.…”
Section: Discussionmentioning
confidence: 99%
“…The deflector approaches were more frequent in the peak flow treatments for both peak flows tested ( Figure 6a 6c, and 6e). Similarly, in a simulated pulsed-flow study conducted in an experimental flume, under increasing flow velocities, three juvenile stream fishes (cyprinid, salmonid, and catastomid) swam faster and also hid in the available rocky substrate, presumably to conserve energy (Chun et al, 2011). Under maximum velocities up to 0.46 m s −1 , those juveniles were able to maintain their swimming speed and hold position (Chun et al, 2011), whereas in the present study, those activities were possible under velocities up to 0.72 m s −1 .…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that access to food would have been a primary motivating factor during our short-term dispersal experiment and more likely that turbulence would have been directly affecting their dispersal path. Observations in flume tanks have suggested that larvae can get temporally disoriented when exposed to turbulent flow (Chun et al 2011), but that this only lasts for a relatively short period (T. Kaminskas, P. Humphries, and H. Keckeis, personal observation).…”
Section: Discussionmentioning
confidence: 99%
“…An important morphological feature of juvenile Chinese sucker that could be related to substrate colour preference is the large dark vertical bars on both sides of the body that remain prominent until fish are several years old (about 30 cm TL). The adaptive significance of these dark bars is unknown, but our data suggest preferring a dark substrate in the day together with the dark body bars may provide camouflage to avoid predators (Guthrie & Muntz, ; Kynard & Horgan, ; Chun et al, ). Darkness of the vertical bars on juveniles changes with light intensity, that is, bars are lighter when light intensity is great (Shi, pers.…”
Section: Discussionmentioning
confidence: 96%
“…Velocity regime has no effect on the strong preference by the free embryo life stage for small gravel substrate (Kynard, Parker, Kynard, & Horgan, ), whereas wintering juveniles strongly preferred fast current in vegetation versus slow current over sand or rocks (Kynard et al, ). For nonsturgeon species, juvenile Sacramento sucker, Catostomus occidentalis , used different substrate among a range of water velocity regimes (Chun et al, ).…”
Section: Discussionmentioning
confidence: 99%